Suberin: A promising renewable resource for novel macromolecular materials - Gandini, Alessandro; Pascoal Neto, Carlos; Silvestre, Armando J. D. (Progress in Polymer Science, 2006)
Suberin, an aliphatic-aromatic cross-linked natural polymer present in the outer tissues of numerous vegetable species, is discussed in terms of (i) its occurrence, particularly where it dominates the bark composition of some trees, (ii) its macromolecular structure and positioning within the cell wall, (iii) its controlled chemical splicing (depolymerization through ester cleavage), (iv) the qualitative and quantitative composition of the ensuing monomeric fragments, and (v) the exploitation of this mixture of monomers in macromolecular science, both as a possible functional additive and as a source of novel materials. The presence of terminal carboxylic and hydroxy groups and of side hydroxy and epoxy moieties on the long chains of suberin ‘‘monomers’’ makes them particularly suited as building blocks for polymers with original architectures and interesting properties
Keywords: Cork; dicarboxylic acids; hydroxyacids; long-chain aliphatic compounds; polyurethanes; suberin

Suberin: A promising renewable resource for novel macromolecular materials - Gandini, Alessandro; Pascoal Neto, Carlos; Silvestre, Armando J D (Progress in Polymer Science, 2006)
Suberin, an aliphatic-aromatic cross-linked natural polymer present in the outer tissues of numerous vegetable species, is discussed in terms of (i) its occurrence, particularly where it dominates the bark composition of some trees, (ii) its macromolecular structure and positioning within the cell wall, (iii) its controlled chemical splicing (depolymerization through ester cleavage), (iv) the qualitative and quantitative composition of the ensuing monomeric fragments, and (v) the exploitation of this mixture of monomers in macromolecular science, both as a possible functional additive and as a source of novel materials. The presence of terminal carboxylic and hydroxy groups and of side hydroxy and epoxy moieties on the long chains of suberin ‘‘monomers’’ makes them particularly suited as building blocks for polymers with original architectures and interesting properties
Keywords: Cork; dicarboxylic acids; hydroxyacids; long-chain aliphatic compounds; polyurethanes; suberin